Specifications and functional impact of a self-triggered grasp neuroprosthesis developed to restore prehension in hemiparetic post-stroke subjects - R. Le Guillou; J. Froger; M. Morin; M. Couderc; C. Cormier; C. Azevedo-Coste; D. Gasq (BioMedical Engineering OnLine, 2024)
Abstract Background Stroke is the leading cause of acquired motor deficiencies in adults. Restoring prehension abilities is challenging for individuals who have not recovered active hand opening capacities after their rehabilitation. Self-triggered functional electrical stimulation applied to finger extensor muscles to restore grasping abilities in daily life is called grasp neuroprosthesis (GNP) and remains poorly accessible to the post-stroke population. Thus, we developed a GNP prototype with self-triggering control modalities adapted to the characteristics of the post-stroke population and assessed its impact on abilities. Methods Through two clinical research protocols, 22 stroke participants used the GNP and its control modalities (EMG activity of a pre-defined muscle, IMU motion detection, foot switches and voice commands) for 3 to 5 sessions over a week. The NeuroPrehens software interpreted user commands through input signals from electromyographic, inertial, foot switches or microphone sensors to trigger an external electrical stimulator using two bipolar channels with surface electrodes. Users tested a panel of 9 control modalities, subjectively evaluated in ease-of-use and reliability with scores out of 10 and selected a preferred one before training with the GNP to perform functional unimanual standardized prehension tasks in a seated position. The responsiveness and functional impact of the GNP were assessed through a posteriori analysis of video recordings of these tasks across the two blinded evaluation multi-crossover N-of-1 randomized controlled trials. Results Non-paretic foot triggering, whether from EMG or IMU, received the highest scores in both ease-of-use (median scores out of 10: EMG 10, IMU 9) and reliability (EMG 9, IMU 9) and were found viable and appreciated by users, like voice control and head lateral inclination modalities. The assessment of the system’s general responsiveness combined with the control modalities latencies revealed median (95% confidence interval) durations between user intent and FES triggering of 333 ms (211 to 561), 217 ms (167 to 355) and 467 ms (147 to 728) for the IMU, EMG and voice control types of modalities, respectively. The functional improvement with the use of the GNP was significant in the two prehension tasks evaluated, with a median (95% confidence interval) improvement of 3 (− 1 to 5) points out of 5. Conclusions The GNP prototype and its control modalities were well suited to the post-stroke population in terms of self-triggering, responsiveness and restoration of functional grasping abilities. A wearable version of this device is being developed to improve prehension abilities at home. Trial Registration: Both studies are registered on clinicaltrials.gov: NCT03946488, registered May 10, 2019 and NCT04804384, registered March 18, 2021.